Polluted Air Increases Perceived Corruption. (5th December 2016) - Huang, Zhenwei; Zheng, Wenwen; Tan, Xuyun; Zhang, Xiaoxiao; Liu, Li
Drawing upon the moral cleanness metaphor and the power height metaphor, we proposed the clear sky effect: polluted air increases perceived corruption. To test the effect, we established a correlation (Studies 1 and 2) and causal link (Studies 3, 4, and 5) between haze pollution and corruption perception. This correlation is unique, in that, of various air pollutants, only the major haze indicator was positively correlated with corruption perception at city (Study 1) and country (Study 2) levels. In addition, recalling feelings concerning haze (Studies 3 and 5) or experiencing hazy days (Study 4) increased corruption perception. Furthermore, in support of embodiment, this effect was moderated by body awareness (Study 4) and mediated by bodily stress responses (Study 5). Taken together, these findings suggest that environmental pollution could be one of the factors that influence our trust in government.